ARTIST (osteoarthritis intervention standardized) study of standardised consultation versus usual care for patients with osteoarthritis of the knee in primary care in France: pragmatic randomised controlled trial. (23rd February 2009) - Ravaud, P; Flipo, R-M; Boutron, I; Roy, C; Mahmoudi, A; Giraudeau, B; Pham, T
Abstract : Objective To evaluate the impact of standardised consultations on patients with osteoarthritis of the knee. Design Open pragmatic cluster randomised controlled trial. Setting Primary care in France. Participants 198 primary care rheumatologists, each of whom had to include two consecutive patients who met the American College of Rheumatology criteria for osteoarthritis of the knee. Interventions Standardised consultation was provided during three goal oriented visits (education on osteoarthritis and treatment management; information on physical exercises; information on weight loss) or usual care. Main outcome measures Change in body weight and in time spent on physical exercises (Baecke index) at four months. Results 336 patients were included (154 allocated to standardised consultation and 182 to usual care). Nine patients were excluded because of lack of baseline data (standardised consultation, n=8; usual care, n=1). At four months, taking into account the clustering effect, the decrease in weight was greater in the standardised consultation group than in the usual care group (mean −1.11 (SD 2.49) kg v −0.37 (2.39) kg; P=0.007). The physical activity score was higher for the standardised consultation group than for the usual care group (mean 0.20 (0.65) v 0.04 (0.78); P=0.013). The standardised consultation and usual care groups did not differ in secondary outcomes, except for global assessment of disease activity (0-10 numeric scale: mean −1.66 (2.26) v −0.90 (2.48); P=0.003) and pain level (0-10 numeric scale: mean −1.65 (2.32) v −1.18 (2.58); P=0.04). Conclusions A structured consultation programme for patients with osteoarthritis of the knee resulted in short term improvement in weight loss and time spent on physical activity. Trial registration Clinical trials NCT00462319 .